Strategies for Improving Waste Management in Solok Regency - Elma Wati; Siti Alya (Institut Pemerintahan Dalam Negeri, 2025)
Waste management in Solok Regency remains constrained by limited infrastructure, low community participation, and inadequate funding, resulting in a significant portion of waste being unmanaged. This research aims to formulate policy strategies to enhance waste management effectiveness by employing descriptive analysis, SWOT analysis, and regulatory review. The results indicate that, while challenges persist, opportunities exist through supportive national regulations, potential collaboration with private and non-governmental actors, and the availability of land for processing facilities. The research concludes that strengthening local regulatory enforcement, expanding TPS3R facilities, and promoting multi-stakeholder and community-based participation are critical to achieving a more sustainable waste management system in Solok Regency.